Influence of Stress Concentration Factor due to Scallop Form on the Wrang Plate Stucture - Riska Arum Dona Kusnadi Putri; Totok Yulianto; Rizky Chandra Ariesta; Mohammad Nurul Misbah (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2022)
The presence of opening in construction is unavoidable for the purpose of reducing stress. A small opening at the construction serves as access to continue the installed construction that runs through the web or girder. However, the presence of the hole also creates an unavoidable problem, the concentration of stress in the area around the hole that will gradually reduce the strength of the ship's construction. Stress concentration occurs due to changes in geometry, causing the flow of stress initially uniformly driven and following the existing geometry. This analysis aims to determine the value of stress concentration factors on the wrang plate due to variations in the shape of scallops. The research method is performed numerically using finite element analysis to find variations in the model with the lowest stress concentration factor. This variation consists of 3 different scallops models with 2 load, drag and press conditions. The values of stress concentration factors are grouped into 3 modes according to mechanical fractures in press loading conditions. Based on the analysis of panel models with compressed loads, it can be seen that model III has the smallest stress concentration factor value in case modes I and III but for mode II the value of the smallest stress concentration factor in model II.